IBM Power systems virtual server guide for IBM i - Quintero, Dino; Abeleira, Jose Martin; Almeida, Adriano; Avalos, Marcelos; Chhabra, Sanjeev; Easlon, Michael; Ferreira, Luis; Hussein, Ahmad Y.; Kesselman, Diego; Jimenez, Gabriel Padilla; Savu, Bogdan; Shetty, Deepak C; et al. (IBM Redbooks, 2022)
This IBM® Redbooks® publication delivers a how-to usage content perspective that describes deployment, networking, and data management tasks on the IBM Power Systems Virtual Server by using sample scenarios. This book addresses topics for IT architects, IT specialists, developers, sellers, and anyone who wants to implement and manage workloads in the IBM Power Systems Virtual Server. This publication also describes transferring the how-to-skills to the technical teams, and solution guidance to the sales team. This book compliments the documentation that available at the IBM Documentation web page and aligns with the educational materials that are provided by IBM Garage for Systems Technical Education.
Keywords: Linux; SAP HANA (Electronic resource); Virtual computer systems; Business enterprises -- Computer networks -- Management; Client/server computing; Information technology -- Management; Systèmes virtuels (Informatique); Entreprises; Réseaux d'ordinateurs; Gestion; Architecture client-serveur (Informatique); Technologie de l'information; Gestion; Business enterprises; Computer networks; Management; Information technology; Management